Genetic and morphological analysis of Berberis microphylla G. Forst. accessions in southern Tierra del Fuego. (4th July 2017) - Giordani, E.; Müller, M.; Gambineri, F.; Paffetti, D.; Arena, M.; Radice, S.
Abstract: Calafate ( Berberis microphylla G. Forst.) is a spontaneous shrub grown in the Patagonian region, from which berries are traditionally harvested for different purposes. This study aims to investigate on the spatial genetic structure of calafate populations grown in southern Tierra del Fuego and their morphological and genetic diversity. A first step of the research focused on 23 putative populations screened by a landscape genetic approach based on 82 geo-referenced and Random Amplified Polymorphic DNA marker characterized plants. The second phase regarded the analysis of the morphological characteristics of fruits, shoots and leaves observed on a subset of 39 plants. Taking into account multiple similarity between pairs and sub-sets of accessions, the observed differences have been associated to geographical and environmental conditions. The results allowed to postulate the existence of homogeneous populations within the studied plant sets and to formulate hypothesis on the evolution of B. microphylla in that area. No association between genetic and morphologic distances of the accessions has been observed.